(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2020)
Uneven level of regional development is something that has characterized Croatia for a long time, with Eastern Croatia lagging behind significantly. There are many indicators that substantiate such a condition as well as the expected trends (e.g. GDP per capita in counties that belong to Eastern Croatia, huge population drain in the region, development index calculated by the Ministry of regional development and many others). As the development level of counties in Eastern Croatia is far from comparable to the most developed ones (especially the City of Zagreb), it is necessary to identify areas for possible improvements in those lagging regions. In the context of the European Union, the development level of counties in Eastern Croatia is particularly low. Other EU members have also failed to achieve convergence towards total homogeneity, but this paper focuses on chosen examples of countries and their regional policies that aimed to decrease existing regional differences. Decentralization level is one of the important prerequisites to decrease existing regional differences and adequately apply regional policies. This paper will theoretically examine the research on experiences of selected EU lagging regions and note the importance of the relationship between regional and national economy. As all five counties in Eastern Croatia can be characterized as lagging counties, one of the goals of this paper is, in accordance with theoretical insights into European experiences, to compare the situation and trends in the lagging regions and counties in Eastern Croatia, going beyond economic considerations to include a much broader context.